The Process of Resolving Criminal Acts of Taking Human Life Based on Hatam Tribe Customs in Manokwari - Saiba, Paulinus; Hammar, Roberth K.R.; Hammar, Imanuel I.R. (IHSA Institute, 2025)
This study analyzes the process of resolving criminal acts of taking human life based on the customary law of the Hatam tribe in Manokwari, employing a normative juridical and socio-legal approach. As a living law sustained through collective legal consciousness, Hatam customary law prioritizes harmony, ancestral values, and restorative justice over retribution. The findings show that the Hatam community classifies the taking of life as a severe violation that disrupts cosmic balance, requiring settlement through customary institutions led by hereditary leaders. Customary sanctions ranging from material fines to ritual purification—aim to restore relationships between families and prevent inter-clan conflict. Through a socio-legal lens, this study demonstrates how customary mechanisms operate in parallel with national criminal law, offering a culturally rooted model of dispute resolution that often proves more effective in achieving lasting peace than formal punitive processes. However, challenges remain in harmonizing customary sanctions with positive law. The study argues for greater formal recognition of customary dispute-resolution mechanisms through regional regulations to strengthen culturally responsive, restorative justice practices within Indonesia’s pluralistic legal system.